2008
DOI: 10.1016/j.ccr.2007.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Coordination polymer networks with s-block metal ions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
164
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(171 citation statements)
references
References 98 publications
2
164
0
1
Order By: Relevance
“…
Abstract: A number of linear coordination polymers have been assembled from lanthanide cations (Ln 3+ ) and cucurbit [7]
…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…
Abstract: A number of linear coordination polymers have been assembled from lanthanide cations (Ln 3+ ) and cucurbit [7]
…”
mentioning
confidence: 99%
“…X-ray diffraction analysis has revealed that they form three groups of isomorphous structures. Generally, the complexes of Q [7] with light lanthanide cations (those with atomic number below that of neodymium (Nd 3+ )) are in one group. The other two groups, in which the lanthanide cation has atomic number greater than that of europium (Eu 3+ ), seem to follow no obvious rule.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The coordination chemistry of alkali metal cations and their interactions with ligands have been widely studied in the past years [7][8][9][10] including the chemistry of molecular clusters [11,12] or macrocyclic compounds [13][14][15]. Many of the obtained complex compounds have potential applications in biological, inorganic, and synthetic chemistry [16,17] and in biotechnology [18].…”
Section: Introductionmentioning
confidence: 99%